The effect of Co and Zn addition on densification and electrical properties of ceria-based nanopowders - Villas-Boas, Lúcia Adriana; De Paula Nascente, Pedro Augusto; Landers, Richard; Campos, Marcelo [UNESP]; De Souza, Dulcina Maria Pinatti Ferreira (FapUNIFESP (SciELO), 2016)
In this work, cobalt and zinc-doped Ce0.8Gd0.2O1.9 samples were prepared starting from a commercial nanopowder and compared to the undoped material. The powder samples were pressed and afterwards sintered by a two-step procedure, before characterization by X-Ray Diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Impedance Spectroscopy (IS) in air. Cobalt or zinc additions are effective as sintering aid, allowing peak sintering temperatures around 1000°C to reach densifications above of 93% of theoretical density, showing no evidence for the presence of secondary phases. The total conductivity at 800 °C of pressed Zn-doped samples (6.7x10-2 S/cm) and Co-doped samples (7.5x10-2 S/cm) is similar for undoped samples (7.2x10-2 S/cm) showing that Zn and Co has a positive effect on densification without compromising the electrical conductivity.
Keywords: Cobalt Addition; Gadolinium-Doped Ceria; SOFC; XPS; Zinc Addition